Organizational Citizenship Behavior Tenaga Penjual: Peran Kepuasan Kerja, Dukungan Rekan Kerja, dan Leader-Member Exchange - Fenika Wulani; Marliana Junaedi (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2020)
This study aims to examine the influence of leader-member exchange (LMX) and coworker support on organizational citizenship behavior (OCB) directed to coworkers, and the mediating role of job satisfaction on these relationships. The respondents of this study were 156 employees who worked as salespeople in various industries in Surabaya. The results of testing using PLS-SEM show that LMX has a significant effect on OCB directed at coworkers, but coworker support does not significantly influence OCB directed at coworkers. LMX and coworker support have effects on job satisfaction, and job satisfaction affects OCB directed to coworkers. Job satisfaction mediates the influence of LMX and coworker support on OCB directed to coworkers. Based on these results, companies need to improve the quality of the relationship between supervisors and subordinates, and between coworkers, such as by conducting training activities for them.